Developing human values and motivation in engineering students using interdisciplinary approach related to the betterment of the world - Shayani, Rafael Amaral (Revista Interdisciplinar de Pesquisa em Engenharia, 2025)
Engineering courses around the world have a high drop-out rate. When students conclude the physics and calculus subjects, most of them get really demotivated. When they face electric engineering subjects, most of them are more concerned about having the minimum grade to pass than to really understand how this knowledge can make them solve real problems of mankind. They are usually more concerned about understanding how things work than to use engineering knowledge to improve the world. Changes in engineering education must take place, especially considering student motivation. The thesis is that students will learn better if they are motivated to use the knowledge to improve the world. Project Based Learning and flipped classroom are improved educational techniques, but these alone will not be enough if the students are still unmotivated to learn. Engineering student must be empowered to solve big mankind problems, as the most of all motivation. This feeling that the student can make a noble contribution to the society will stimulate them to learn in an active way. Using also active teaching techniques, the classroom will change to a flourishing learning place. The United Nations Sustainable Development Goals are presented to the students as challenges that the knowledge from the class should empower them to couple with. The SDG gives an open-minded interdisciplinary view to engineering student. This educational approach has been carried out on Electrical Engineering classes at University of Brasilia, and more than 98% of the students reported that they developed human values.